Determination of macronutrients and trace elements in potential nickel hyperaccumulators from ultramafic areas in Sabah using atomic spectroscopic analysis - Salim, Nur Syafiqah; Ag Nuddin, Julenah; Md Buang, Matsain; Sumail, Sukaibin; Ent, Antony van der; Echevvaria, Guillaume (Faculty of Applied Sciences, 2025)
Hyperaccumulators species are widely distributed on ultramafic lands where it is capable to accumulate extremely high concentration of metalloids such as Ni, Co and Mn in the above-ground parts without showing any signs of toxicity. However, related information on identified hyperaccumulators from Sabah such as elemental distribution is insufficient due to lack of fundamental studies. The aim of this study is to contemplate hypernickelophores as tropical metal crop candidate for sustainable metal farming and environmental cleanup through evaluation of macronutrients and trace elements such as Na, Ca, K, Ni, Co and Mn in identified hyperaccumulators using Atomic Absorption Spectrophotometer (AAS). 8 species of previously identified hyperaccumulating plants (Psychotria sarmentosa, Glochidion sp. ‘bambangan’, Rinorea, bengalensis, Rinorea javanica, Actephila alenbakeri, Walsura pinnata, Xylosma luzonensis and Mischocarpus sundaicus were collected from serpentinite area in Kinabalu Park for this study. 4 hypernickelophores which are G. sp. ‘bambangan’, R. bengalensis, R. javanica and P. sarmentosa were found with the accumulation of Ni as much as 10 784 mg/kg, 13 196 mg/kg, 13 780 mg/kg and 17 085 mg/kg, respectively. These findings suggest that these species hold promise for phytoremediation and phytoextraction in Malaysia, particularly in regions with ultramafic soils. Therefore, further study on G. sp. ‘bambangan’ should be carried out as it is an undescribed taxon which is endemic to Sabah. Apart from that, it is crucial to determine the most suitable agronomic practices for the hypernickelophore so the metal bioavailabilty can be increased. Therefore, it can be utilized in the application of metal farming which is a novel mineral extraction technology.